Analisis Unsur Intrinsik dan Ekstrinsik Pada Novel “Bidadari Bermata Bening” Karya Habiburrahman El Shirazy - Nurul Rahmah (PT. Alahyan Publisher Sukabumi, 2025)
This study aims to analyze the intrinsic and extrinsic elements of the novel Bidadari Bermata Bening written by Habiburrahman El Shirazy. The novel presents themes of a Muslim woman’s dignity and obstructed love, with the main character Ayna portrayed as a principled and resilient figure. The intrinsic elements analyzed include theme, characters and characterization, setting, plot, point of view, moral message, and language style. Meanwhile, the extrinsic elements cover the author’s biography, psychological background, social and cultural environment, as well as the values and philosophies reflected in the work. This research applies a descriptive qualitative method with a structural approach, aiming to thoroughly explore the narrative structure and embedded messages. The findings reveal that both intrinsic and extrinsic elements contribute cohesively to the novel’s overall meaning, reinforcing the religious and moral characteristics that are distinctive of El Shirazy’s literary style. The novel not only presents a narrative of love and struggle but also serves as a medium of Islamic da'wah that touches readers’ spiritual and social awareness.